2000
DOI: 10.1007/s002130050029
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among dopamine transporter affinities and cocaine-like discriminative-stimulus effects

Abstract: Rationale: The discriminative-stimulus effects of cocaine have been reported to be mediated by indirect agonist actions initiated by the blockade of dopamine uptake, and the potencies of drugs that have discriminativestimulus effects like cocaine are directly related to their dopamine transporter binding affinities. The binding to the dopamine transporter by cocaine and many of its analogs has been reported to fit better using a two-site model than a one-site model. Objectives: The present study examined the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…We replicated previous findings that the present DA uptake inhibitors (e.g., Broadbent et al, 1991;Baker et al, 1993;Kleven et al, 1999;Katz et al, 2000) and DA releasers substitute completely for cocaine (e.g., D'Mello and Stolerman, 1977;Risner et al, 1985;Wood and EmmettOglesby 1988;Ukai et al, 1993;Young and Glennon, 1993;Koetzner et al, 1996). When DA uptake inhibitors and DA releasers were given before or concurrently with cocaine, the cocaine dose-effect function was shifted to the left, with a trend toward a change in the slope of the dose-effect curve.…”
Section: Discussionsupporting
confidence: 88%
“…We replicated previous findings that the present DA uptake inhibitors (e.g., Broadbent et al, 1991;Baker et al, 1993;Kleven et al, 1999;Katz et al, 2000) and DA releasers substitute completely for cocaine (e.g., D'Mello and Stolerman, 1977;Risner et al, 1985;Wood and EmmettOglesby 1988;Ukai et al, 1993;Young and Glennon, 1993;Koetzner et al, 1996). When DA uptake inhibitors and DA releasers were given before or concurrently with cocaine, the cocaine dose-effect function was shifted to the left, with a trend toward a change in the slope of the dose-effect curve.…”
Section: Discussionsupporting
confidence: 88%
“…, a specific DAT ligand (K d of 0.9 nM for the high-affinity DA uptake site) (Vignon et al, 1988;Katz et al, 2000). Nonspecific binding was determined from two adjacent sections by adding 1 M GBR12935 to the binding buffer.…”
Section: Quantitative Autoradiographymentioning
confidence: 99%
“…Nomifensine and GBR 12909 are specific DA reuptake blockers and yet their effect is more similar to amphetamine than to methylphenidate. Therefore, the differences in the effect of amphetamine and methylphenidate on DA neuron activity could be due to other factors dictating the in vivo effects of these drugs (e.g., differences in bioavailability, brain pharmacokinetics, binding to different sites, potency to block the dopamine transporter; Katz et al, 2000). Interestingly, some investigators have reported that nomifensine has the properties of a DA releaser (Hurd and Ungerstedt, 1989) and weak DA receptor agonist (Gianutsos et al, 1982) in addition to pure transporter blocker (e.g., methylphenidate).…”
Section: Downloaded Frommentioning
confidence: 99%